2017
DOI: 10.1111/acel.12698
|View full text |Cite
|
Sign up to set email alerts
|

Sirt2‐BubR1 acetylation pathway mediates the effects of advanced maternal age on oocyte quality

Abstract: SummaryThe level of Sirt2 protein is reduced in oocytes from aged mice, while exogenous expression of Sirt2 could ameliorate the maternal age‐associated meiotic defects. To date, the underlying mechanism remains unclear. Here, we confirmed that specific depletion of Sirt2 disrupts maturational progression and spindle/chromosome organization in mouse oocytes, with compromised kinetochore–microtubule attachments. Candidate screening revealed that acetylation state of lysine 243 on BubR1 (BubR1‐K243, an integral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 45 publications
4
50
0
Order By: Relevance
“…Consequently, in oocytes from Sirt2 Tg/+ overexpressing animals, increases in kinetochore – microtubule stability likely contributed to augmented chromosome alignment and improved fertility. These observations are corroborated by separate in vitro studies where morpholino-mediated Sirt2 knockdown or chemical inhibition of SIRT2 in oocytes resulted in severe spindle defects and chromosome disorganization (29, 38). These results are supported by the apparent lower rates of aneuploidy in oocytes from aged Sirt2 Tg/+ animals in the present study.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Consequently, in oocytes from Sirt2 Tg/+ overexpressing animals, increases in kinetochore – microtubule stability likely contributed to augmented chromosome alignment and improved fertility. These observations are corroborated by separate in vitro studies where morpholino-mediated Sirt2 knockdown or chemical inhibition of SIRT2 in oocytes resulted in severe spindle defects and chromosome disorganization (29, 38). These results are supported by the apparent lower rates of aneuploidy in oocytes from aged Sirt2 Tg/+ animals in the present study.…”
Section: Discussionsupporting
confidence: 52%
“…4i), indicating that at a younger age where NAD is replete, SIRT2 is not essential for accurate spindle assembly, or that there is redundancy in the role of SIRT2 with other yet to be identified factors. These in vivo results from Sirt2 knockout animals are in contrast to studies of in vitro morpholino knockdown of Sirt2 (28) or chemical inhibition of SIRT2 in oocytes (38), where depletion or inhibition results in spindle assembly defects and aneuploidy (28, 29). The discrepancy between these results may be due to the compensatory, upregulation of other factors in constitutive knockout animals, versus the acute depletion of SIRT2 in oocytes during in vitro maturation.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Oocytes from whole-body Sirt2 À/À knockout mice at the age of 5-6 months displayed normal spindle assembly and maturation ( Figure 3I), indicating that at a younger age at which NAD + is replete, SIRT2 is not essential for accurate spindle assembly or that redundancy exists in the role of SIRT2 with other yet-to-be-identified factors. These in vivo results from Sirt2 knockout animals are in contrast to in vitro studies (Qiu et al, 2018;Riepsamen et al, 2015;Zhang et al, 2014). Altogether, (D and E) Aged (12-to 14-month-old) transgenic mice overexpressing NMNAT1 have increased oocyte yield (*p = 0.0416, two-tailed t-test, n = 8-10 per group) (D) in comparison to transgenics overexpressing NMNAT3 (n = 7-11) (E).…”
Section: Controlmentioning
confidence: 92%
“…One candidate that we hypothesized for this role is the NAD + -dependent deacylase SIRT2. We previously showed that SIRT2 stabilizes the SAC protein BubR1 (North et al, 2014), which is critical for meiotic progression (Homer et al, 2009), kinetochore attachment, and chromosome segregation in oocytes (Qiu et al, 2018;Touati et al, 2015;Zhang et al, 2014). Levels of BubR1 decline in mouse reproductive tissue (North et al, 2014) and human oocytes with advancing age (Riris et al, 2014).…”
Section: Controlmentioning
confidence: 99%